The Hereditary Basis of Rheumatic Diseases - Holmdahl, Rikard; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2006)
Rheumatoid Arthritis (RA) represents a complex disease where the inheritable component has been estimated to be up to 60%. This PIR volume deals with the genetic basis and regulation of rheumatic diseases. The first part of the book describes genetic studies on rheumatic diseases. The second part deals with the shared heredity of rheumatic diseases, e.g., RA, lupus and ankylosing spondylitis. The third part of the volume describes tools for analysing genetic complexity, ranging from animal models to new molecular tools. The volume is essential reading for researchers and clinicians from rheumatology, inflammation research, immunology, and cell and molecular biology. .
Genetics of joint inflammation — problems and possibilities -- Genetic studies on rheumatic diseases -- The epidemiology of rheumatoid arthritis and the use of linkage and association studies to identify disease genes -- Heterogeneity in rheumatoid arthritis based on expression analysis: towards personalised medicine -- Gene-based large scale LD-mapping of rheumatoid arthritis-associated genes -- Shared heredity of rheumatic diseases -- Emerging relationships: rheumatoid arthritis and the PTPN22 associated autoimmune disorders -- Shared genes in rheumatic diseases, the role of PD1 and the RUNX genes in disease susceptibility -- The role of B27 and other genes associated with ankylosing spondylitis -- Tools for analysing complexity -- Emerging tools for dissecting complex disease -- Expression analysis of rheumatic diseases, prospects and problems -- The use of humanized MHC mouse strains for studies of rheumatic diseases -- SKG mice, a monogenic model of autoimmune arthritis due to altered signal transduction in T-cells -- A genetic approach to select and validate new targets for treatment of rheumatic diseases.
Keywords: Rheumatology; Immunology; Human genetics; Cell biology; Rheumatology; Immunology; Human Genetics; Cell Biology